PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIb SMP NEGERI 4 PERANAP - Rika Aprilia; Yenita Roza; Rini Dian Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research based on low mathematics learning achievement of student class VIIb SMPN 4 Peranap. Percentage of students reach KKM is 39,29%. The research was classroom action research. This research aims to improve learning process and student outcome by implementing cooperative lerning model structural approach of Think Pair Square (TPS). There are 28 students in the class, consisting 13 boys and 15 girls. The instrumen of data collection on this research are observation sheets for activities of teachers and students and math achievement tests. The observation sheets of teachers and students are analyzed qualitatively while the math achievement tests are analyze quantitative. The qualitative analysis showed an improvement of learning process prior to treatment of the first cycle to the second cycle. The result of this research showed an increase in student from the based score with the persentage 39,29%, to 64,29% on the first test and 75% on the second test. From the result of this study concluded that cooperative learning model structural approach of Think Pair Square can improve the students learning achievement at class VIIb SMPN 4 Peranap in the second semester academic years 2015/2016.Key Word : Mathematics learning outcome, cooperative learning model structural approach of think pair square, class action research